2002
DOI: 10.1177/03635465020300031001
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and Laxity of the Knee Joint after Anterior Cruciate Ligament Reconstruction

Abstract: Kinematics of the anterior cruciate ligament injured knee did not change significantly after ligament reconstruction, but the functional results were satisfactory and knee laxity was diminished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 25 publications
7
107
2
4
Order By: Relevance
“…In vivo studies with three-dimensional motion analysis from our laboratory [4][5][6] have demonstrated abnormal rotational knee movement during highly demanding activities after reconstruction of the anterior cruciate ligament. Our results have been verified by both in vitro and in vivo studies from other laboratories 2,7,[11][12][13][14] . Furthermore, authors of in vitro studies have examined the possible causes of this phenomenon and have investigated the effects, on rotational knee kinematics, of the configuration and placement of the graft used to reconstruct the anterior cruciate ligament.…”
Section: Level Of Evidence: Therapeutic Level II See Instructions Tosupporting
confidence: 82%
See 2 more Smart Citations
“…In vivo studies with three-dimensional motion analysis from our laboratory [4][5][6] have demonstrated abnormal rotational knee movement during highly demanding activities after reconstruction of the anterior cruciate ligament. Our results have been verified by both in vitro and in vivo studies from other laboratories 2,7,[11][12][13][14] . Furthermore, authors of in vitro studies have examined the possible causes of this phenomenon and have investigated the effects, on rotational knee kinematics, of the configuration and placement of the graft used to reconstruct the anterior cruciate ligament.…”
Section: Level Of Evidence: Therapeutic Level II See Instructions Tosupporting
confidence: 82%
“…This parameter is measured clinically with the Lachman test or the anterior drawer test 1 . However, rotational knee movement after injury and reconstruction of the anterior cruciate ligament is difficult to quantify [2][3][4][5][6][7] . The only clinical test for examining rotation is the pivot-shift test, which is a subjective static measurement that can mask small rotational differences between the intact and the reconstructed knee.…”
Section: Level Of Evidence: Therapeutic Level II See Instructions Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal knee rotation occurs after ACL injury and is not corrected by conventional single-bundle (SB) ACL reconstruction [1,8,13,15,29,30,32,33]. Abnormal knee kinematics (translations, rotations) has been implicated in the initiation and progression of knee osteoarthritis secondary to altered normal joint contact [5].…”
Section: Introductionmentioning
confidence: 99%
“…Even with modern reconstruction techniques, it has not yet proven possible to demonstrate a lower incidence of OA in operated individuals (25,26) .…”
Section: Anterior Cruciate Ligament Reconstruction Using the Double-bmentioning
confidence: 99%